Labour market liberalization and the rise of dualism in Europe as the interplay between governments, trade unions and the economy. (8th October 2020) - Simoni, Marco; Vlandas, Tim
Abstract: Why have labour market reforms varied so much across European countries in the 30 years preceding the economic crisis? We argue that the degree of liberalization over time in each country depends on the interaction between governments' partisan leaning, the strength of trade unions and the economic problem‐load pushing governments to adopt distinct labour market reform strategies. Building on existing literature, we interpret 'dualizing' labour market reforms as weaker forms of liberalization and test our argument on the cross‐national variation in over 200 labour market reforms carried out in 14 western European countries between 1985 and 2007. Our empirical results show that governments are less likely to liberalize if they face a strong union movement and the economic problem‐load is low. However, even in countries with strong unions, opposition may not always manage to block change. First, as unemployment becomes more severe, unions' ability to reduce the likelihood of liberalization strongly decreases. Second, trade unions often do not manage to prevent liberalization advanced by social democratic governments. Third, governments can devise three (non‐rival) strategies to deflect opposition: (1) they can re‐regulate parts of the labour market to protect certain workers from liberalization; (2) generous unemployment benefits can cushion the costs of liberalization, thereby increasing its likelihood; and (3) they can carry out two‐tier reforms to insulate insider (unionized) workers employed in permanent contracts, which limits union opposition. By identifying the complex interactions between variables that explain variation in labour market liberalization across European countries, this article contributes to our understanding of the evolution of European political economy.